Assessment of Physical Factors in the Work Environment as an Effort to Analyze Health Risks of Indonesian Informal Worker - Hutapea, Octavianus; Ayu, Friska; Rhomadhoni, Muslikha Nourma; Sunaryo, Merry (Universitas Nahdlatul Ulama Surabaya, 2025)
The sandal industry is one of the industries that poses health risks to workers, particularly due to the physical conditions of the work environment and the production process, which serve as potential hazards. One form of control that can be implemented is the measurement of physical factors in the workplaces. Therefore, the purpose of this study was to measure the physical hazard factors, specifically noise and lighting, and to describe the potential health risks faced by workers in a shoe manufacturing company in Surabaya. This research employed an observational analytic design with a cross-sectional approach, involving 25 respondents selected using a total sampling technique. The study was conducted from Juli to August 2024. Data on respondents’ characteristics were collected through interviews using a questionnaire, while blood pressure was measured using an Omron digital sphygmomanometer. Blood pressure was assessed before and after work on the same day. Physical factors in the work environment, such as noise, were measured using a sound level meter, and lighting was measured using a lux meter. The results showed that the average noise level range from 80.5-82.4 dBA, which l does not exceed the threshold limit value (TLV) of 85 dBA according to the Minister of Manpower Regulation No. 5 of 2018 concerning Occupational Safety and Health in the Work Environment. The average lighting level 107.8 lux, which is below the minimum lighting standard for sewing activities, s (500-700 lux), based on the Minister of Health Regulation No. 70 of 2016 concerning Standards and Requirements for Environmental Health in Industrial Workplaces. Health examinations showed an increase in average systolic and diastolic blood pressure s among the workers. Further examination is required to determine whether physical factors in the work environment contribute to the observed increase in blood pressure among workers in the sandal and shoe industry. Keywords: Work environment measurement, Industrial Hygiene, Occupational Health, Informal Sector, Safety